The Phaidra Experience II - Budroni, Paolo (Septentrio Conference Series, 2014)
Subtitle: A project for the permanent storing of digital objects at the University of Vienna “Open Access is not only defined as offering unfettered access to scientific literature, but also – and above all – free access to the very instrument of publication itself. The content provider in research (the owner of the digital objects) should always have the ability to publish digital objects and assign usage licenses to them and without bureaucratic restrictions.” (Phaidra Policy) Phaidra, an acronym for Permanent Hosting, Archiving and Indexing of Digital Resources and Assets, is an all-university digital asset management system with permanent storing functions. Phaidra provides a technological basis for the realization of the Berlin Declaration on Open Access to Knowledge in the Sciences and Humanities, which was signed on January 26, 2010, by the Rector of the University of Vienna at that time. In the development of Phaidra, the challenge of alternative Nobel Prize-winner Harold Varmus was observed, which stipulates that a majority of research is financed by taxes – and the impending results are then to be made public. Phaidra is an “open” system. Not only in that it was developed based on open source software, but access to the system is available without restrictions to all members of the University of Vienna – teachers and students. The active use of Phaidra, that is, the storing and linking of objects – without bureaucratic obstacles (red tape) – is open to users with a mailbox account, typically employees of the University of Vienna, as well as externals who obtain permission, and students with a u:net account. Searching and viewing the contents – if desired – is possible worldwide without logging in. All members are permitted to invite guests (guest accounts).